BIO083: Biology For Pre Science / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2022)
This course involves the basic concepts and principles of biology that cover on the surface information about cells structure, component and function, basic animal and plant tissue, structure and function, organ structure and functions, basic concept of nutrition in organism such as for example digestive process in human and photosynthesis process in plant. Throughout the course students will be equipped with basic knowledge in biology that is very important for the detail biology process during the diploma and degree level.